No Evidence of Systematic Change of Physical Activity Patterns Before and During the Covid-19 Pandemic and Related Mood States Among Iranian Adults Attending Team Sports Activities - Aghababa, Alireza; Zamani Sani, Seyed Hojjat; Rohani, Hadi; Nabilpour, Maghsoud; Badicu, Georgian; Fathirezaie, Zahra; Brand, Serge (Frontiers in Psychology, 2021)
Objective: To cope with the Coronavirus Disease 2019 (COVID-19) pandemic health authorities released social restrictions. Such social restrictions impacted on the people’s possibilities to move deliberately in public space and to gather with other people. In the present study, we investigated the impact of COVID-19-related restrictions (“confinement”) on physical activity (PA) patterns before and during the confinement among team sports participants. Such PA patterns were further related to current mood states, and possible sex-differences were also explored. Methods: A total of 476 adults exercising team sport (football, futsal, volleyball, handball and basketball; mean age: 24.66 years; 48.1% females) completed a series of self-rating questionnaires covering sociodemographic information, former and current PA patterns, and current mood states. Results: Compared to the period before the confinement, PA intensity decreased, but PA frequency increased during the confinement. Past, current and changes in physical activity patterns were unrelated to participants’ mood states. Sex differences in mood were spurious. Sex differences in physical activity patterns were modest, with male participants reporting a higher physical activity intensity during the confinement. Conclusions: The present pattern of results suggests that the COVID-19-related confinement did not impact in a uniform fashion on PA patterns of adults attending team sports. Further, mood states were unrelated to current physical activity patterns. Given the complex psychosocial situation of COVID-19-related confinement, it appeared very unlikely that sole physical activity patterns could counterbalance possible impaired states of mood and behavior.